Gasless laparoendoscopic single-site assisted extracorporeal ovarian cystectomy through the umbilicus for the management of ovarian torsion at 33 weeks of gestation: A case report with literature review - Akihiro Takeda; Shotaro Hayashi (Elsevier, 2023)
Ovarian torsion in the third trimester of pregnancy is a rare but potentially dangerous non-obstetric complication for both mother and fetus and presents a diagnostic and therapeutic challenge for the treating physicians. A 39-year-old woman (gravida 2, para 1) presented at 7 weeks of gestation. Asymptomatic bilateral small ovarian cysts were diagnosed at the initial presentation. Progesterone was intramuscularly administered every 2 weeks after 28 weeks of gestation because of uterine cervical length shortening. Sudden onset of right lateral abdominal pain was reported at 33 weeks and 2 days of gestation. Emergency laparoendoscopic single-site (LESS) surgery was performed through the umbilicus under strong suspicion of right adnexal torsion with ovarian cyst, as indicated by magnetic resonance imaging a day after admission. Isolated right ovarian torsion without fallopian tube involvement was identified under laparoscopic view. The contents of the right ovarian cyst were aspirated after confirming resumption of color tone of the right ovary after detorsion. Then, the right adnexal tissue was grasped through the umbilicus, followed by a successful ovarian cystectomy under direct vision. Tocolysis was postoperatively attempted by intravenous ritodorine hydrochloride and magnesium sulfate administration, which was continued through to 36 weeks and 4 days of gestation, because of increased uterine contraction frequency. The next day, spontaneous labor occurred, followed by the vaginal delivery of a healthy 2108-g female infant. The postnatal course was uneventful. Transumbilical LESS-assisted extracorporeal ovarian cystectomy is a feasible and minimally invasive option for ovarian torsion management in the third trimester of pregnancy.